Impact of Plant Harvesting on Soil Properties and Carbon Storage in Canal Command area of Indian Desert - Singh, G.; Choudhary, G. R.; Limba, N. K.; Purohit, Neha; Bala, N. (Indian Forester, 2023)
Impact of clear-felling on nutrient and soil organic carbon (SOC) depletion was assessed in plantations of Indira Gandhi Nahar Pariyojana (IGNP) area of western Rajasthan for devising management strategies and maintaining carbon sink. Twenty-eight-year-old stands of E. camaldulensis and Vachellia tortilis were evaluated for trees densities, height and diameter at breast height (DBH), stand biomass and soil properties in 2018 and changes in soil characteristics and carbon stock were monitored after clear-felling. E. camaldulensis and V. tortilis stands had 630M100.9 (mean ± SE) and 194±10.30 tree ha-1 and dry biomass of 333.61±53.1 and 119.58±36.1 Mg ha-1 respectively. In 2018, soil under E. camaldulensis showed low bulk density (BD) and highest pH, EC, SOC, SOC stock and available nutrients. Control plot showed highest BD and lowest other soil variables. Except BD, pH and EC (increased in deep soil layers), other variables were highest in 0-25 cm soil layer and decreased downward. In 0-75 cm soil layer, SOC stock was 16.36 Mg ha-1 in control that increased by 1.5-fold in V. tortilis and 3.3-fold in E. camaldulensis plantations. After clear-felling, average soil pH increased by 0.58 unit, whereas EC, SOC, NH4-N, NO3-N, PO4-P and SOC stock decreased by 33.0%, 51.5%, 63.0%, 56.8%, 51.8% and 40.7% respectively in 2021 than in 2018. Depletion in nutrients and SOC stock was greater in E. camaldulensis and least in control plots and deeper soils showed higher depletions. In conclusion, plantations of IGNP are important carbon stock, which was significantly affected under clear felling. Maintaining these plantations on such marginal lands by limited harvesting may be recognized as a management action for reducing land degradation and offsetting terrestrial C emission.